Mismatch Shocks and Unemployment During the Great Recession - Francesco Furlanetto; Nicolas Groshenny (Norges Bank, 2013)
We investigate the macroeconomic consequences of fluctuations in the effectiveness of the labor-market matching process with a focus on the Great Recession. We conduct our analysis in the context of an estimated medium-scale DSGE model with sticky prices and equilibrium search unemployment that features a shock to the matching efficiency (or mismatch shock). We find that this shock is almost irrelevant for unemployment fluctuations in normal times. However, it plays a somewhat larger role during the Great Recession when it contributes to raise the actual unemployment rate by 1.25 percentage points and the natural rate by 2 percentage points. Moreover, it is the only shock that generates a positive conditional correlation between unemployment and vacancies
hdl:11250/2496691
Keywords: E32; C51; C52; 330; search and matching frictions; unemployment; natural rates